2009
DOI: 10.5194/npg-16-431-2009
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic solitary waves in current layers: from Cluster observations during a super-substorm to beam experiments at the LAPD

Abstract: Abstract. Electrostatic Solitary Waves (ESWs) have been observed by several spacecraft in the current layers of Earth's magnetosphere since 1982. ESWs are manifested as isolated pulses (one wave period) in the high time resolution waveform data obtained on these spacecraft. They are thus nonlinear structures generated out of nonlinear instabilities and processes. We report the first observations of ESWs associated with the onset of a super-substorm that occurred on 24 August 2005 while the Cluster spacecraft w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…34,35,37 This assumption is needed, because the solitary wave polarity and the direction of propagation could not be disentangled from one another. 38 However, space observations also revealed the presence of large negative potential structures, with the density perturbation, Dn=n, being negative. 23,24 That also agreed with the theory, which predicted that ion-acoustic double layers are typically negative but required the presence of a second electron component.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…34,35,37 This assumption is needed, because the solitary wave polarity and the direction of propagation could not be disentangled from one another. 38 However, space observations also revealed the presence of large negative potential structures, with the density perturbation, Dn=n, being negative. 23,24 That also agreed with the theory, which predicted that ion-acoustic double layers are typically negative but required the presence of a second electron component.…”
Section: Introductionmentioning
confidence: 95%
“…senses and on different timescales, implying the possible presence of solitons and double layers of both polarities, for both lower frequency (ion) and higher frequency (electron) structures. 26,33,36,38 The observation of both polarities could follow in a more general plasma, if the satellite passes from one plasma region to another and changes in the plasma parameter values cause the nonlinearity coefficient in the KdV equation to change sign. Furthermore, both polarities could occur if the plasma conditions are fairly similar in two observation periods, but they happen to support coexistence, and the two polarities are excited in neighboring regions due to differences in the local conditions in space and time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other interpretations put forward for the generation of ESWs are based on electron-acoustic solitary waves [3,4,5]. Recently, the plasma measurements made on the Cluster spacecraft in the PSBL have shown that broadband (∼ 2-6 kHz) electrostatic noise is associated with cold countersteaming electron beams flowing through the hot Maxwellian plasma [6,8]. The observed plasma parameters were (from Ref.…”
Section: Introductionmentioning
confidence: 95%
“…The velocities of ESWs can vary from ∼ a few hundred to a few thousand km s −1 . Electrostatic solitary structures have been observed in the almost all regions of the Earth's magnetosphere [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%